Breastfeeding, Blood Pressure Control, and Maternal Outcomes in Postpartum Women with Preeclampsia: A Prospective Cohort - Yenny Puspitasari; Reni Yuli Astutik; Agusta Dian Ellina; Astri Yunita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Preeclampsia remains a major contributor to maternal morbidity and mortality, particularly during the postpartum period. Effective blood pressure control and optimal breastfeeding practices may play important roles in maternal recovery, yet evidence on their combined effects remains limited. This study aimed to examine the association between breastfeeding practices and blood pressure control with maternal outcomes among postpartum women with preeclampsia. A prospective cohort study was conducted among 120 postpartum women diagnosed with preeclampsia in selected hospitals in Kediri Regency, Indonesia, between July and December 2024. Participants were selected using simple random sampling from a population of 185 eligible women. Data collection was performed at baseline (?48 hours postpartum) and follow-up visits at weeks 1, 2, 4, and 6 postpartum. Breastfeeding practices were assessed using a structured questionnaire, while blood pressure was measured using standardized procedures. Maternal outcomes included recovery status, persistence of hypertension, complications, and hospital readmission. Multivariable logistic regression analysis was conducted using SPSS. Blood pressure decreased significantly over the postpartum follow-up period. Women with good breastfeeding practices at 6 weeks postpartum had significantly higher odds of favorable maternal outcomes compared to those with suboptimal practices (AOR = 2.41; 95% CI: 1.12–5.18; p = 0.024). Controlled blood pressure was the strongest predictor of favorable outcomes (AOR = 3.76; 95% CI: 1.65–8.54; p = 0.002). Severity of preeclampsia was also significantly associated with maternal outcomes (AOR = 2.89; 95% CI: 1.31–6.39; p = 0.008). Breastfeeding practices and effective blood pressure control are important factors associated with improved maternal outcomes among postpartum women with preeclampsia. Strengthening integrated postpartum care, including continuous monitoring and breastfeeding support, is essential to optimize maternal recovery and reduce complications